ISLAMIC RELIGIOUS EDUCATION IN HIGHER EDUCATION IMPLEMENTATION OF SCIENCE AND SOCIAL CHANGE - Nahuda, Nahuda (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: Islamic Religious Education (PAI) plays a critical role in shaping students' character and morals, not only by imparting knowledge of Islamic teachings but also by instilling spiritual and ethical values that influence social behavior. Purpose: Given ongoing social transformations, such as technological advancements and cultural shifts, the importance of PAI has become more pronounced. Globalization and modernization present both opportunities and challenges, including moral decay, identity crises, and social conflicts. In this context, PAI serves as a moral guide, helping students navigate these complexities. Method: This study, using a qualitative research method with a phenomenological approach, aims to inform the improvement of PAI teaching quality and highlight its significance in addressing evolving societal dynamics. Result: The findings show that PAI fosters moral responsibility and social awareness among students, equipping them to face modern challenges. Moreover, integrating contemporary pedagogical methods with traditional Islamic teachings enhances PAI's effectiveness in shaping students' character in an era of rapid social and technological change.